(untitled) (LEARNing Landscapes, 2015)
This exploratory paper describes the collaborative planning, reflection, and teaching for two teacher educators in the process of professional development and acclimation to new faculty positions in a College of Education. As a result of intense and reflective conversations, they discovered a mutual interest in the writings of Schön (1987) and found that his work on uncertainty, uniqueness, and value conflict served as a useful heuristic for understanding their shared experience of co-teaching a curriculum course. Their experiences of reflection in and on action, and their subsequent commitment to changes in their practice as teacher educators, are told in a narrative format to help other college educators see the personal as well as professional growth and development that occurred for both.